Communication Strategies in a Medical Setting: Overcoming Language Barriers at the Pain Clinic of RSUD Genteng Banyuwangi - Ketut Santi Indriani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates doctor–patient communication strategies in overcoming verbal and non-verbal language barriers within the Pain Clinic of RSUD Genteng Banyuwangi, a public hospital in East Java, Indonesia. Pain clinics pose unique communicative challenges, as patients often struggle to express their discomfort clearly due to limited health literacy, cultural norms, or emotional inhibitions. This research aims to identify and analyze the communicative methods employed by doctors to facilitate accurate information exchange and build therapeutic rapport with patients experiencing chronic pain. Utilizing a qualitative approach, this study applies Conversation Analysis (CA) to naturally occurring doctor–patient consultations recorded through non-intrusive video methods. Verbal and non-verbal interactions were transcribed and analyzed to uncover recurring communicative patterns. The data were interpreted through sociolinguistic and pragmatic lenses to account for the local language diversity and cultural context of Banyuwangi. Findings reveal that doctors employ multiple strategies to clarify meaning and adapt communication: repetition, strategic questioning, utterance correction, and linguistic adaptation. Additionally, doctors interpret and respond to patients' non-verbal cues, including vocal tone, facial expressions, and body gestures, to supplement incomplete verbal communication. These strategies not only enhance diagnostic accuracy but also promote empathy, trust, and patient-centered care. The study concludes that effective communication in pain clinics must account for linguistic diversity, cultural sensitivities, and emotional dynamics. Adaptive and empathetic communication fosters better understanding, reduces the risk of diagnostic error, and improves treatment outcomes. The findings offer practical implications for clinical training and healthcare policy, particularly in multicultural and linguistically diverse settings.